2002
DOI: 10.1159/000065599
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Nature of Spontaneous Age-Related Eye Lesions Observed in a 2-Year Inhalation Toxicity Study in Rats

Abstract: A group of 160 Wistar rats (both sexes) from a larger chronic inhalation toxicity study was monitored at baseline and after 1 and 2 years with a photo-slitlamp microscope and a direct ophthalmoscope to record spontaneous age-related eye lesions and treatment-related eye lesions over a period of 24 months. A second group from the same study was monitored at the start and after 5 months of a 6-month posttreatment period immediately following the inhalation period. Rats were nose-only exposed for 6 h/day, 7 days/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 5 publications
1
13
1
Order By: Relevance
“…increased exposure to pollen due to anti-desertification projects). So far, family history and sensitization to house-dust mites, pollen and other airborne allergens [15,16,17] have been identified as possible risk factors for asthma. Interestingly, a high prevalence of vitamin D deficiency in women, reportedly related to asthma in offspring [18,19], has also been found among Emirati women of child-bearing age [20].…”
Section: Introductionmentioning
confidence: 99%
“…increased exposure to pollen due to anti-desertification projects). So far, family history and sensitization to house-dust mites, pollen and other airborne allergens [15,16,17] have been identified as possible risk factors for asthma. Interestingly, a high prevalence of vitamin D deficiency in women, reportedly related to asthma in offspring [18,19], has also been found among Emirati women of child-bearing age [20].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, few studies have shown the effects of DEP on the ocular mucosa. [11][12][13] Inhabitants of cities are exposed to high levels of air pollutants, including DEP, and often present irritation, burning, foreign body sensation, hyperemia, and itching in the eye. 14 They also show a reduced time of rupture of the tear film and slight damage to the surface layer of the cornea.…”
mentioning
confidence: 99%
“…Pollen from members of the Arecaceae (Palmaceae), in particular the date palm ( P. dactylifera L.), can cause allergic symptoms, especially among people living in Middle Eastern, North African and some Mediterranean countries, as well as in India [1,2,3,4,5,6,7,8,9,10,11]. Previous papers evidenced the presence of several allergens in DP pollen extract, the more clinically relevant being those at 14, 25, 28–30, 37–40, 55–70 and 90–100 kDa [12, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of date palm (DP, Phoenix dactylifera ) pollen and pollen from other members of the palm family as potent inhalant allergens has been reported from different areas of the world where these palms grow [1,2,3,4,5,6,7,8,9,10,11]. The intense influx of immigration from these countries to Italy where there is an abundance of autochthonous palm tree species, such as the European fan palm (EFP, Chamaerops humilis ), could in the near future increase the risk for sensitized migrating people of developing allergic symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation